1989
DOI: 10.1093/ageing/18.4.258
|View full text |Cite
|
Sign up to set email alerts
|

Age and the Pharmacokinetics of Morphine

Abstract: Eight healthy young and nine healthy elderly volunteers received 10 mg morphine sulphate as an intravenous infusion, an oral solution and a slow-release tablet (MST Continus, Napp Laboratories) on three separate occasions. Pharmacokinetic profiles of morphine base were measured over a 24-h period using 13 sampling times. The elderly group showed decreased morphine clearance with a trend to a smaller volume of distribution. They achieved higher maximum plasma concentrations (Cmax) after both oral formulations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(45 citation statements)
references
References 0 publications
1
42
0
2
Order By: Relevance
“…An age-related decrease in opioid self-administration has been well-documented (Burns et al, 1989;Giuffre et al, 1991;Macintyre and Jarvis, 1995;. This has been attributed to age-related increases in the analgesic efficacy of opioids (Kaiko, 1980;Mqore et al, 1990) which may be secondary to agerelated changes in morphine metabolism (Owen et al, 1983;Baillie et al, 1989;Laizure et al, 19931, Van Crugten et al, 1997). Unfortunately, the current study did not assess morphine pharmacology, making it impossible to determine the role of this factor in the differences observed.…”
Section: Discussionmentioning
confidence: 99%
“…An age-related decrease in opioid self-administration has been well-documented (Burns et al, 1989;Giuffre et al, 1991;Macintyre and Jarvis, 1995;. This has been attributed to age-related increases in the analgesic efficacy of opioids (Kaiko, 1980;Mqore et al, 1990) which may be secondary to agerelated changes in morphine metabolism (Owen et al, 1983;Baillie et al, 1989;Laizure et al, 19931, Van Crugten et al, 1997). Unfortunately, the current study did not assess morphine pharmacology, making it impossible to determine the role of this factor in the differences observed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the dose requirements for drugs, including morphine, decreased with increasing age [6][7][8]. Baillie et al [6] reported that oral doses of morphine produced higher plasma concentrations in elderly volunteers (mean age, 74 years) than in young volunteers (mean age, 27 years), because fi rst-pass metabolism and clearance in the elderly group had decreased.…”
Section: Discussionmentioning
confidence: 99%
“…It is available in both immediate- and slow-release preparations. However, it has variable bioavailability, may need extra vigilance in the elderly and in renal dysfunction and has potential side effects in many patients [38,39,40]. …”
Section: Why Use Morphine?mentioning
confidence: 99%